Effect of A Clinical-Replicable Cooling Protocol on the Cyclic Fatigue Resistance of Heat-Treated Nickel-Titanium Instruments - Heck, Luana; Weissheimer, Theodoro; Souza Calefi, Pedro Henrique; Priori Alcalde, Murilo; Ricci Vivan, Rodrigo; da Rosa, Ricardo Abreu; Hungaro Duarte, Marco Antonio; Reis SÃ³, Marcus Vinicius (Iranian Endodontic Journal, 2022)
Introduction: The aim of this study was to evaluate the bending and cyclic fatigue resistance of Wave One Gold (WOG) and X1 Blue (X1B) instruments when tested at body temperature (36° ± 1°C) subjected or not to an alloy cooling protocol. Methods and Materials: Twenty instruments of each system (n=40) were selected and divided into two groups: body temperature (BT); body temperature with cooling protocol (CP). Cyclic fatigue test was performed until fracture in a custom stainless-steel device with water bath equipment to simulate body temperature. CP group instruments were subjected to 5 seconds of spray cooling at every 30 seconds. Time to fracture was recorded. Resistance to bending at 45o was evaluated using ten instruments of each system. Fractured surfaces were examined under scanning electron microscopy (SEM). Statistical analysis was performed using Student t test at 5% significance level. Results: WOG instruments had significantly less cyclic fatigue resistance compared to X1B instruments in BT (P=0.00001) and CP (P=0.0001) groups. Significantly increased resistance was observed in X1B instruments (P=0.0003) and in WOG (P=0.0003) when cooling protocol was applied. There were no significant differences between the values of resistance increase presented by the instruments after cooling (P>0.05). Bending test presented no statistically significant differences between the tested instruments (P>0.05). Both instruments in both groups showed typical features of cyclic fatigue behavior under SEM. Conclusions: Cooling protocol extended the cyclic fatigue resistance of both instruments.